Starch isolation from chestnut and acorn flours through alkaline and enzymatic methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Food and Bioproducts Processing, 2012)
Two different procedures were used to isolate chestnut (Castanea sativa Mill.) and acorn (Quercus suber) starch. Starch was extracted from the ﬂour of these dried fruits by: (i) low shear at alkaline pH and successively using three sieves (A3S) at different centrifugation conditions (velocity and time) and (ii) enzymatic treatment at low shear (ENZ) at a different amount/digestion time of protease. In both cases a Central Composite Rotatable Design (CCRD) was used as an experimental design. Results were treated through the Response Surface Methodology (RSM). Based on maximum yield values and the degree of purity, the best modiﬁed conditions encountered were applied in a new trial and mass balance was established for both isolation procedures. The best centrifugation conditions encountered for the A3S isolation method were 800 × g during 15min, and for the ENZ method 900 units of protease despite the incubation time, for the same centrifugation terms. The yields reached with these experimental conditions for the A3S and ENZ methods were 83.9% and 79.9% for chestnut and 88.5% and 86.9% for acorn, respectively. Isolated starches shown to be higher in purity, presented values of 98.3% and 96.3% for chestnut and 98.1% and 97.6% for acorn, respectively for the A3S and ENZ methods
The following values have no corresponding Zotero field: publisher: Institution of Chemical Engineers
Keywords: acorn; chestnut; composition; isolation method; starch; yield

Combination of structural and compositional factors for describing forest types using national forest inventory data - Rego, F; Godinho-Ferreira, P; Uva, J S; Cunha, J (Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality, 2005)
For the first time in Portugal, simple variables describing the vertical structure and the composition of forests on the Portuguese mainland were included in the 2258 sample plots of the National Forest Inventory (DGF 2001). The vertical forest structure was assessed by percentage cover of seven height. classes and the composition of the different layers was described using plant species, or groups of plant species, easily identifiable in the field. Cluster analysis, in particular K-means statistics, was performed using combinations of vertical structure and compositional data, resulting in ten main natural groups or forest types: 1) Quercus pyrenaica forests; 2) Other deciduous oak forests; 3) Arbutus unedo forests; 4) Cistus shrubs; 5) Cytisus shrubs; 6) Acacia forests; 7) Quercus suber forests; 8) Pinus pinaster forests; 9) Eucalyptus forests; and 10) Other forests. The last four groups were further subdivided according to the vertical structure resulting in twenty final forest types. The geographical distribution of these forests types and the implications for biodiversity and other forest issues are presented and discussed.
Keywords: Biodiversity; composition; forest types; national forest inventory; vertical structure

Combination of structural and compositional factors for describing forest types using national forest inventory data - Rego, F.; Godinho-Ferreira, P.; Uva, J. S.; Cunha, J. (Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality, 2005)
For the first time in Portugal, simple variables describing the vertical structure and the composition of forests on the Portuguese mainland were included in the 2258 sample plots of the National Forest Inventory (DGF 2001). The vertical forest structure was assessed by percentage cover of seven height. classes and the composition of the different layers was described using plant species, or groups of plant species, easily identifiable in the field. Cluster analysis, in particular K-means statistics, was performed using combinations of vertical structure and compositional data, resulting in ten main natural groups or forest types: 1) Quercus pyrenaica forests; 2) Other deciduous oak forests; 3) Arbutus unedo forests; 4) Cistus shrubs; 5) Cytisus shrubs; 6) Acacia forests; 7) Quercus suber forests; 8) Pinus pinaster forests; 9) Eucalyptus forests; and 10) Other forests. The last four groups were further subdivided according to the vertical structure resulting in twenty final forest types. The geographical distribution of these forests types and the implications for biodiversity and other forest issues are presented and discussed.
The following values have no corresponding Zotero field: periodical: Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality issue: 51 pub-location: TORIKATU 34, FIN-80100 JOENSUU, FINLAND
Keywords: Biodiversity; composition; forest types; national forest inventory; vertical structure

Cork and Alcoholic Beverages - Maga, Joseph A; Puech, Jean-Louis (Food Reviews International, 2005)
For centuries, cork has been the stopper of choice for various alcoholic beverages. In this review, cork history, sources, production, physical properties, composition, off-flavors, and alternatives to cork stoppers are discussed.
doi: 10.1081/FRI-200040593
Keywords: Alternatives; composition; production; Properties; stoppers; Taint

Cork and Alcoholic Beverages - Maga, Joseph A.; Puech, Jean-Louis (Food Reviews International, 2005)
For centuries, cork has been the stopper of choice for various alcoholic beverages. In this review, cork history, sources, production, physical properties, composition, off-flavors, and alternatives to cork stoppers are discussed.
doi: 10.1081/FRI-200040593doi: 10.1081/FRI-200040593The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Alternatives; composition; production; Properties; stoppers; Taint